PENGARUH INTELLECTUAL CAPITAL TERHADAP (ERC) EARNING RESPONS COEFFICIENT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Indra Saputra; Sri Mulyani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This purpose of this research was to found whether effect Intellectual Capital against on the earning response coefficiet (ERC) within banking company which registered in Indonesia Stock Echange. The theory used in this research is the theory of market efficiency. The dependent variable in this study is the cumulative abnormal return (CAR), and variable the independent variables are standardized unexpected earnings (SUE),and intellectual capital that uses the measurement of Value Added Intellectual Coefficient ( VAIC ). The sample drawn by purposive sampling and fulfill sample selection criterion. In order to analized connection between Intellectual Capital to earning response coefficiet (ERC) by used multiple linear regression analysis. Research result showed that variable of Intellectual Capital have relation to earning response coefficiet (ERC).